The good housekeeping illustrated cookbook - Good Housekeeping (New York Hearst Books, 1989)
America's bestselling step-by-step cookbook, with more than 1,400 recipes
D., 02/2006, Ronald & Adele St Pierre in Memory of Irene M St Pierre
Keywords: Cookery -- Preparation of food with and without the use of heat